Actinomycosis of the ileocaecal junction - Agrawal, R K; Kumar, B; Agarwal, M; Regmi, R; Khania, S; Adhikary, S; Agrawal, C S (Health Renaissance, 2012)
No abstract available. DOI: http://dx.doi.org/10.3126/hren.v10i2.6590 Health Renaissance 2012; Vol 10 (No.2); 157-159